The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3390/jof9030351
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Ribonucleotide Reductase Is a Direct Target of the Proteasome and Provides Hyper Resistance to the Carcinogen 4-NQO

Abstract: Various external and internal factors damaging DNA constantly disrupt the stability of the genome. Cells use numerous dedicated DNA repair systems to detect damage and restore genomic integrity in a timely manner. Ribonucleotide reductase (RNR) is a key enzyme providing dNTPs for DNA repair. Molecular mechanisms of indirect regulation of yeast RNR activity are well understood, whereas little is known about its direct regulation. The study was aimed at elucidation of the proteasome-dependent mechanism of direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Our data provide new evidence of the similarity between the mechanisms of RNR activity regulation in yeast and mammals. So, we have previously shown that the yeast subunit Rnr1 [23], as well as its orthologue in mammalian cells RRM1 [35], serves as a substrate of the proteasome. Since RRM2, the ortholog of the yeast Rnr2 subunit, is controlled in a cell cycle phase-dependent manner by the ubiquitin-proteasome system [34,57], we can assume that the yeast Rnr2 subunit also serves as a proteasome substrate under DNA-damaging stress.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our data provide new evidence of the similarity between the mechanisms of RNR activity regulation in yeast and mammals. So, we have previously shown that the yeast subunit Rnr1 [23], as well as its orthologue in mammalian cells RRM1 [35], serves as a substrate of the proteasome. Since RRM2, the ortholog of the yeast Rnr2 subunit, is controlled in a cell cycle phase-dependent manner by the ubiquitin-proteasome system [34,57], we can assume that the yeast Rnr2 subunit also serves as a proteasome substrate under DNA-damaging stress.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that Rnr1p is a substrate of the proteasome [23], which is evidenced by an increase in the content of Rnr1p under the action of the proteasome inhibitor bortezomib or in a mutant strain with reduced proteasome activity due to decreased expression of the PRE1 gene encoding an essential structural subunit of the proteasome (called pre1-8). In the present study, Western blot analysis showed that in the mutant strain rpn4-Δ with the deletion of the RPN4 gene, which encodes a key transcriptional regulator of proteasomal genes [45][46][47], an increase in the level of the large catalytic subunit of ribonucleotide reductase Rnr1p was also observed under normal conditions (Figure 1A,B), while the level of RNR1 mRNA did not change significantly (Figure 1C).…”
Section: Rnr Subunit Levels Are Elevated In Strains With Impaired Pro...mentioning
confidence: 99%
See 3 more Smart Citations